Volunteer Behavior: A Hierarchical Model Approach for Investigating Its Trait and Functional Motive Antecedents - Mowen, John C.; Sujan, Harish (Journal of Consumer Psychology, 2005)
We investigated the antecedents of volunteer behavior within a hierarchical model of motivation and personality. In Study 1, we developed measures of altruism and volunteer orientation and combined them with three additional traits to predict a set of volunteer behaviors. In Studies 2 and 3, we added six functional motives for volunteering identified by Clary et al. (1998) to the model. Across the 3 studies, the traits of altruism, the need for activity, and the need for learning were consistent predictors of volunteer orientation. In Studies 2 and 3, the measure of volunteer orientation was a significant predictor of the functional motives and of volunteer behaviors. Furthermore, the motive to help others was positively related to volunteering behaviors, and the motive of self‐enhancement was negatively related to them. Overall, the results support the proposal that functional motives act like motivated reasons for acting and reside at the surface level in a hierarchical model of personality.